2017
DOI: 10.1186/s12906-017-1735-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activities of selected Sudanese medicinal plants on Porphyromonas gingivalis and matrix metalloproteinase-9 and isolation of bioactive compounds from Combretum hartmannianum (Schweinf) bark

Abstract: BackgroundPeriodontal diseases are one of the major health problems and among the most important preventable global infectious diseases. Porphyromonas gingivalis is an anaerobic Gram-negative bacterium which has been strongly implicated in the etiology of periodontitis. Additionally, matrix metalloproteinases-9 (MMP-9) is an important factor contributing to periodontal tissue destruction by a variety of mechanisms. The purpose of this study was to evaluate the selected Sudanese medicinal plants against P. ging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…gingivalis . Fabaceae and Asteraceae were the two most represented botanical families, which has also been found in other studies [ 55 , 56 ] thus indicating the need to further investigate these families; albeit, this might be due to an overrepresentation of these families as they are the two largest botanical families in the world.…”
Section: Discussionsupporting
confidence: 75%
“…gingivalis . Fabaceae and Asteraceae were the two most represented botanical families, which has also been found in other studies [ 55 , 56 ] thus indicating the need to further investigate these families; albeit, this might be due to an overrepresentation of these families as they are the two largest botanical families in the world.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies on the plant reported the antimicrobial activity of its extracts and fractions . Terminalia brownii is one of the most important plants in treatment of tick‐borne diseases and is known to have antibacterial activity aganist Porphyromonas gingivalis …”
Section: Discussionmentioning
confidence: 99%
“…Terminalia brownii is known with its antibacterial and antioxidant properties, and the use of smoke from Acacia seyal is associated with an increased risk of visceral leishmaniasis (phlebotomus make peak activities in thickets of Acacia seyal). [3][4][5][6][7][8][9][10][11][12][13]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations